Intracranial Bleeding as a Major Problem Among Neonates With Disseminated Intravascular Coagulation After the Introduction of Recombinant Thrombomodulin. Issue 3 (28th April 2022) - Taguchi, Yosuke; Yagasaki, Hiroshi; Nagano, Nobuhiko; Fuwa, Kazumasa; Morioka, Ichiro
Abstract : A standard treatment for disseminated intravascular coagulation in neonates has not yet been established. We analyzed the outcomes of 23 neonates who developed disseminated intravascular coagulation due to infection or asphyxia between 2004 and 2017. The overall survival rate was 95.7% on day 28 after anticoagulant therapy. In contrast, the bleeding-free survival rate was 69.6% (95% confidence interval, 53.1%-91.2%). Of the 6 neonates with intracranial bleeding, 2 developed neurological sequelae. The current study showed that intracranial bleeding remained a major problem in the early 2000s, despite the introduction of a new anticoagulant drug, recombinant thrombomodulin, at our institution since 2009.